(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The article presents the ethnography of the third edition of the scenic “Tiradentes Court”, which aims to be a symbolic trial and a political act against the Legal system imposed by the Brazilian civil - military dictatorship (1964-1985). In this version, the Amnesty Law enacted in 1979, which pre- vents the prosecution of state agents accused of committing human rights violations, was judged. The memory of those affected by state terrorism during the democratization pro- cess in the country was essential to the conviction of the Amnesty Law in this symbolic court. However, in the offi- cial courts “auto amnesty” is kept, guided by the memory of the Military forces according to which the law was the result of a broad social consensus. In this respect, the Bra- zilian reality becomes Kafkaesque, with its sentinels of law preventing access to justice in democratic times.